DESIGN AND DEVELOPMENT OF BLUETOOH CONTROLLED ROBOT BYUSING SOLAR POWER - Dr.B.MOULI CHANDRA; N.LEELA VASAVI; MUTTHARASU NAGA ABHISHEK; NUSUM VENKATESWARA REDDY; KOLLA PAVAN TEJA; GUNJA VAMSI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Robotic Bluetooth control powered by solar energy is used in this project. The entire procedure is managed via a Bluetooth Android app. The directions in the Bluetooth Android app are L, R, B, F, and S. Robot will move in the directions of left, right, front, and rear depending on the instruction issued through an Android Bluetooth app. Robot will go left if we click the Bluetooth Android app's "L" button. Similar to this, the robot will travel in the appropriate way if we click on the Bluetooth Android app "R." The robot will move in the same way if we click on the Bluetooth Android app "F," and it will move in the back if we click on the Bluetooth Android app "B." Human effort will be decreased by using this